Preparation and property of extremely stable superhydrophobic carbon fibers with core-shell structure. (September 2019) - Feng, Shizhan; Luo, Wanxia; Wang, Luxiang; Zhang, Su; Guo, Nannan; Xu, Mengjiao; Zhao, Zongbin; Jia, Dianzeng; Wang, Xingchao; Jia, Lixia
Abstract: Superhydrophobic materials have a wide range of applications in oil/water separation, controlled corrosion and self-cleaning. However, most superhydrophobic polymer materials are surface-modified with fluorides or silicides, these materials will lose their superhydrophobic properties when exposed to strong acid, strong base or high temperatures. Herein, superhydrophobic carbon fibers (SCFs) with a core-shell structure have been prepared by electrospinning technology combined with subsequent chemical vapor deposition (CVD). The addition of oxidized coal (OC) increases the diameter of the fibers, while the CVD process achieves a graphitic carbon layer with low surface energy, ultimately resulting in a water contact angle (CA) as high as 159.5°. The as-prepared SCFs can effectively separate a series of oil/water mixtures with large flux and high separation efficiency. The SCFs have the ability to repel contamination of sand, orange juice, coffee and plant chlorophyll extract. What's more, the SCFs could maintain superhydrophobicity at the temperature of 97 °C under the corrosive liquid. In addition, the SCFs still maintain excellent superhydrophobicity after impregnating in strong acid, strong alkali and organic solvents for 120 days. The SCFs can be used repeatedly under various harsh conditions for a long time and may have a wide application prospect in the future. Graphical abstract: Image 1